Mikovirus, Pengembangannya sebagai Agens Pengendali Hayati - Supyani Supyani (Universitas Gadjah Mada, 2017)
Mycoviruses are viruses that infect fungus. In plant pathogenic fungi, mycoviruses infection may cause hypovirulence. Therefore, mycoviruses could be developed as biological control agents against the plant pathogenic fungi. Abroad, mycoviruses have long been studied and developed into biological control agents. So far, many mycoviruses have been and are being developed as biological control agents. One that has been successfully manipulated is the Cryphonectria hypovirus 1 to control blight disease on chestnut trees (Castanea dentata). In Indonesia, in brief, mycoviruses has not been sufficiently investigated. This article is aimed to introduce mycoviruses in Indonesia, as well as to inform that a study on mycoviruses has been underway in the country IntisariMikovirus adalah virus yang menginfeksi jamur. Pada jamur patogen tumbuhan, infeksi mikovirus dapat menyebabkan hipovirulen. Dengan demikian mikovirus dapat dikembangkan sebagai agens pengendali hayati terhadap jamur patogen tumbuhan. Di luar negeri mikovirus sudah sejak lama dikaji, diantaranya adalah untuk dikembangkan sebagai agens pengendali hayati. Sampai sekarang sudah banyak mikovirus yang telah/sedang dikembangkan sebagai agens pengendali hayati. Salah satu yang sudah berhasil adalah Cryphonectria hypovirus 1 untuk mengendalikan penyakit hawar kastanye (Castanea dentata). Di tanah air, mikovirus dapat dibilang belum dikaji secara memadai. Artikel ini bertujuan untuk memperkenalkan mikovirus di tanah air, sekaligus menginformasikan rintisan kajian mikovirus yang telah dilakukan di tanah air.